The revolving door and worker flows in banking regulation - David Lucca; Amit Seru; Francesco Trebbi (Federal Reserve Bank of New York, 2014)
Drawing on a large sample of publicly available curricula vitae, this paper traces the career transitions of federal and state U.S. banking regulators and provides basic facts on worker flows between the regulatory and private sectors resulting from the revolving door. We find strong countercyclical net worker flows into regulatory jobs, driven largely by higher gross outflows into the private sector during booms. These worker flows are also driven by state-specific banking conditions as measured by local banks' profitability, asset quality, and failure rates. The regulatory sector seems to experience a retention challenge over time, with shorter regulatory spells for workers, and especially those with higher education. Evidence from cross-state enforcement actions of regulators shows that gross inflows into regulation and gross outflows from regulation are both higher during periods of intense enforcement, though gross outflows are significantly smaller in magnitude. These results appear inconsistent with a "quid pro quo" explanation of the revolving door but consistent with a "regulatory schooling" hypothesis.
Keywords: G21; G28; 330; banking regulation; revolving door; inter-industry worker flows